Sclerosing Stromal Tumor: A Rare Ovarian Neoplasm - Shilpa Bairwa; Rahul Satarkar; Shivani Kalhan; Shilpa Garg; Ashok Sangwaiya; Pawan Singh (Iranian Society of Pathology, 2017)
Ovarian sex cord-stromal tumors are relatively infrequent neoplasms that account for approximately 8% of all primary ovarian neoplasm. Sex cord-stromal tumors of the ovary include granulosa cell tumors, fibrothecomas, Sertoli-Leydigcell tumors, steroid cell tumors, and sclerosing stromal tumors (SST). Sclerosing stromal tumors account for 2% to 6% of ovarian stromal tumors. Despite the rarity of this particular neoplasm, it is not always possible to predict the presence of this tumor preoperatively on the basis of clinical and sonographic findings. Histopathological and immunohistochemical (IHC) examinations confirm the diagnosis. Herein, the clinical findings and histopathological features of SST are described in a 24-year-old female.